Axonal electrovisiogram as an electrophysiological test to evaluate optic nerve and inner retina electrical potentials: findings in normal subjects - Cella,Wener Passarinho (2011)
PURPOSES: To standardize and validate the technique of axonal electrovisiogram (AxEvg), defining its normative values and parameters and characterizing its findings in normal individuals. METHODS: We enrolled 140 normal individuals (280 eyes) divided into seven groups according to age, each one with 10 males and 10 females. The technique was based on monocular visual stimulation by a 0 dB intensity bright flash on Ganzfeld bowl at a presentation rate of 1.4 Hz. Golden cup electrodes were used and electrical waves were acquired after artifact rejection. For each amplitude and implicit time peak we calculated the mean, median, pattern deviation, minimum and maximum values and 95% confidence interval. RESULTS: Monocular visual stimulation with bright flash under mesopic conditions was the standard technical procedure established. The normal AxEvg waveform consists of an initial positive wave (named P1, with mean amplitude of 2.0 mV and mean implicit time peak of 23.1 ms) followed by a negative wave (named N1, with mean amplitude of -3.9 mV and mean implicit time peak of 41.4 ms). No significant differences were observed between males and females or between right and left eyes, but there was an increased P1 and N1 implicit time peaks according to age. Implicit time characteristics suggest that P1 wave represents an optic nerve electrical potential and N1 wave represents an inner retinal layers potential. CONCLUSIONS: AxEvg can be considered a pre-chiasmatic visual evoked potential capable to reliably record the electrical activity of optic nerve and inner retina. The findings suggest that AxEvg may be useful as an electrophysiological test in the diagnosis of neuroretinal diseases.